Frequency of Esophagogastric Anastomotic Leakage in Esophageal Cancer: A Retrospective Study of 4 Year Period in Nishtar Hospital Multan - Muhammad Kaleem Ullah, Muhammad Sami Ullah, Maria Angbeen Hashmi, Ayesha Tariq, Mansoor Ali, Muhammad Raza, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Esophagogastric anastomotic leakage is a major complication after esophagectomy for esophageal cancer that contributes to increased morbidity, prolonged hospitalization and death. Objective: The objective of this study is to evaluate the incidence of cervical esophagogastric anastomotic leakage in patients undergoing esophagectomy for esophageal cancer at the Nishtar Hospital Multan as well as associated risk factors and outcomes in these patients. Methodology: A retrospective study in 94 patients who had undergone esophagectomy with cervical esophagogastric anastomosis for cancer of the esophagus was performed from July 2019 to June 2023. Patient data were collected on demographics data, surgical approach, operative time, blood loss, postoperative complications and outcomes. Anastomotic leakage was diagnosed on clinical signs, radiological findings and surgical interventions. Results: Anastomotic leakage developed in 12.7% in cervical anastamosis. The median time of detection of leakage was 5 days (range 3-10 days) after surgery. Conservative management was tried in all the patient of anastamotic leakage. The average length of stay of the cases of leakage was 14.2+-5.6 days while it was 10.1+-3.4 in non-leaks. Death in the patients with leakage occurred in 8.33%. Conclusion: Esophagogastric anastomotic leakage is a common and catastrophic complication in cervical esophagectomy. Early detection, rapid intervention and pre-operative optimisation of nutrition plays an important role in up comes of these patients. Keywords: Esophagectomy, Cervical Esophagogastric anastomosis, Anastomotic leakage, Esophageal cancer, Surgery, Morbidity, Mortality.